Literature Review of Behavioral Counseling Interventions in Addressing Behavioral and Psychological Problems - Qawiyyan Fitri; Farida Aryani; Siska Putri Ayu; Salsabila Nasution; Sinta Nurul Oktaviana Kasim; Nurni’mah (ILIN Institute, 2026)
This study aims to analyze the trends in the application of behavioral counseling techniques in addressing various behavioral and psychological problems, as well as to map the suitability between clients’ problem characteristics, the use of ABC behavioral analysis (Antecedent, Behavior, Consequence), and the selection of behavioral intervention techniques. This study is important because most previous studies have primarily focused on the application of a single behavioral technique to a specific type of problem, while comprehensive studies synthesizing multiple behavioral techniques within contemporary guidance and counseling practices remain limited. This study employed a literature review approach using content analysis methods on scientific articles and journals published within the last five years. The findings indicate that modeling, assertive training, relaxation, systematic desensitization, and behavior contract techniques demonstrate different patterns of application depending on the characteristics of the problems addressed. In addition, ABC analysis plays an important role in determining appropriate interventions by identifying the relationship between antecedents, behaviors, and consequences. The study reinforces the relevance of behavioral counseling as a systematic, measurable, and adaptive approach in contemporary guidance and counseling services.